The Sacrality of the Secular: Postmodern Philosophy of Religion - Onishi, Bradley B. ca. 20./21. Jh. (Columbia University Press, 2018)
As philosophers in the continental tradition have taken an interest in the return of religion, anthropologists and sociologists have rejected the once-dominant secularization thesis. Bradley B. Onishi connects these lines of thought to reveal how philosophy's religious investigations have enabled critical reflections on the category of the secular